Pengendalian Pemanfaatan Ruang di Wilayah Kabupaten Dati II - Ibrahim, Syahrul (Journal of Regional and City Planning, 1998)
The implementation of physical development does not always in harmony with the spatial plan. Diversion in function or spatial use can occur due to various factors such as operational factor, administrative/political factor and market development. This condition indicated that spatial use control is needed in order to achieve consistency between spatial use and spatial plan. This article will discuss practical approach n actions needed in monitoring and controlling spatial use, including the granting of development permit. Since the scope of discussion is intended for Kabupaten Dati II understanding the object of control which has different levels becomes important. Those, levels are: block plan, site plan, zoning and pattern and structural plan. The control should start from the lowest to the highest level, strictly and consistently. The agency responsible for the control should be chosen based on the levels: therefore, should there be any diversion, the responsible agency can be known immediately. The control is conducted through inspection and investigation on the spatial diversion. The sanction can be administrative or criminal. This control and sanction will be effective if conducted by a Special Team involving related agencies.